The role of the aryl hydrocarbon receptor in Helicobacter pylori infection - Traulsen, J (2023)
The gastric pathogen Helicobacter pylori is a master of immune evasion and the main risk factor for developing non-cardia gastric cancer. The bacterium has evolved numerous strategies to evade the immune response launched by the infected host, enabling it to persist on the epithelium of the stomach for decades, despite chronic inflammation of the stomach mucosa. While many evasion mechanisms have been discovered, it is unknown as of yet, how the bacterium evades the strong NF-κB-driven inflammatory response that follows sensing of the bacterium by the gastric epithelium. The aryl hydrocarbon receptor is an important regulator of homeostasis and has been shown to modulate the inflammatory response by regulating pro-inflammatory signalling pathways such as the one mediated by NF-κB. We therefore hypothesized that activation of the AHR by H. pylori could lead to inhibition of the NF-κB-driven inflammatory response, which would enable a novel strategy to eradicate H. pylori without the use of antibiotics through inhibition of AHR. In this study we demonstrate that loss of AHR led to decrease of H. pylori burden in infected AHR-deficient mice, possibly preventing the progression of gastritis. AHR-deficient mice demonstrated reduction of bacteria and did not develop mucosal hyperplasia, as opposed to wild-type mice. We also demonstrate that H. pylori activates the AHR in human epithelial cells and leads to increased AHR expression in human corpus tissue. Additionally, we show that AHR-deficient murine epithelial cells displayed an increased pro-inflammatory response to infection compared to wild-type cells and that this was potentially mediated by TNF-α. When attempting to increase the epithelial NF-κB response through inhibition of AHR however, we found that this did not lead to an increase in NF-κB activation, but that this effect could still be obtained by knockout of AHR in a human epithelial cell line.